Erosion protection of low‐concentration fluoride on human tooth enamel: results from surface morphology and nanomechanical and anti‐wear properties. Issue 3 (28th October 2020) - Zheng, Liang; Shi, Maoyu
Abstract : Dental erosion results in excessive tooth wear. The contribution of low‐concentration fluoride used daily in the prevention and treatment of erosion has not been fully understood. In this study, the effects of fluoride (225 ppm F − ) on the surface morphology and nano‐mechanical and anti‐wear properties of human tooth enamel were investigated to explore whether low‐concentration NaF solution could help protect tooth enamel from erosion. In total, 40 enamel samples were divided into 5 groups, viz. group O: original surface with no treatment, group F: fluoride treatment (NaF, 225 ppm F −, pH 6.3), group E: erosion treatment (0.001 M citric acid, pH 3.2, 3 min), group EF: erosion treatment and then fluorination and group FE: fluoride treatment and then erosion. The mechanical and anti‐wear properties of enamel samples were examined using a nano‐indentation/scratch technique. Both surface morphology and scratch morphology of enamel samples were observed with scanning electron microscopy. The results showed that, from the perspectives of surface morphology and anti‐wear properties, fluorination with low‐concentration fluoride (225 ppm F − ) before erosion has a certain potential for protection against dental erosion. Fluoride treatment after erosion has no obvious impact on the remineralisation of eroded enamel.